2008
DOI: 10.1007/s10620-008-0467-8
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Surgery Affects Small Bowel Transit Time and Completeness of Capsule Endoscopy

Abstract: The aim of the study was to evaluate bowel dysmotility in patients with a history of abdominal surgery by measuring both gastric transit time and small bowel transit time during capsule endoscopy and assessing the completeness of the examination. The study included 26 patients who had undergone abdominal surgery (postoperative group) and 52 patients who had not (control group). The capsule reached the cecum in 50.0% of the postoperative group and 80.8% of the control group (P=0.005). While there was no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Inaccordancewithotherreports,wefoundthatthemain reasonforincompleteSBexaminationistheprolongedcapsulestayinginatractproximaltothepylorus (7)(8)(9)(10)(11)(12)(13).Hospitalization, type 2 diabetes mellitus, and previous abdominal surgery are known conditions associated with incompleteSBexamination.Prokinetics(32)andchewing gum (33) prior to the procedure have been advocated to overcome these drawbacks, but there are no double-blind randomizedtrialstoprovetheireffectiveness,andarecent single-blindprospectivetrialofmetoclopramidewasdisappointing (34).Concerningtheotherriskfactors,ourcontrol group of younger patients was well matched not only for genderandclinicalindicationtoSBCEbutalsofordiabetes mellitus, previous abdominal surgery, and comorbidity, suggestingthatagingmaybeagenuineriskfactorforSBCE failure.…”
Section: Diagnostic Yield and Findingssupporting
confidence: 68%
See 1 more Smart Citation
“…Inaccordancewithotherreports,wefoundthatthemain reasonforincompleteSBexaminationistheprolongedcapsulestayinginatractproximaltothepylorus (7)(8)(9)(10)(11)(12)(13).Hospitalization, type 2 diabetes mellitus, and previous abdominal surgery are known conditions associated with incompleteSBexamination.Prokinetics(32)andchewing gum (33) prior to the procedure have been advocated to overcome these drawbacks, but there are no double-blind randomizedtrialstoprovetheireffectiveness,andarecent single-blindprospectivetrialofmetoclopramidewasdisappointing (34).Concerningtheotherriskfactors,ourcontrol group of younger patients was well matched not only for genderandclinicalindicationtoSBCEbutalsofordiabetes mellitus, previous abdominal surgery, and comorbidity, suggestingthatagingmaybeagenuineriskfactorforSBCE failure.…”
Section: Diagnostic Yield and Findingssupporting
confidence: 68%
“…Ontheotherhand,CEisexpensiveanditsuseinclinical practicehastobeoptimized.Inparticular,foragoodyield oftheprocedure,twoissuesarecritical:theappropriateness ofclinicalindicationandtheexclusionofthosepatientscarryingahighriskoffailure.Althoughonlyfewstudiesaddressedtheriskfactorsforincompletesmallbowelcapsule endoscopy(SBCE),hospitalization,slowgastricemptying, previousabdominalsurgery,anddiabetesmellitusseemto berelatedtoapoorperformanceandalowerrateofcompleteness (6)(7)(8)(9)(10).Notsurprisingly,inasmallstudyofpatients with established chronic intestinal dysmotility, the completionrateofSBCEwasonly61% (11).Age,asavar-iableofSBCEperformance,hasbeenevaluatedintwostudies,withdifferentcriteriaandresults.Inthefirst,Fireman andco-workers (12),inaretrospectiveanalysisofalarge multicenter database, showed that people more than 40 yearsoldhavealongerSBtransittime;inthesecond,Papadopulos and co-workers (13) failed to demonstrate any significantdifferenceofSBtransittimeamongthreeagerelatedgroups(<40,40-65,and≥65)ofaprospectiveco-hortof120patients.…”
mentioning
confidence: 99%
“…Estimation using VCE transit time is effective, but advancing VCE speed can change due to the presence of obstacles or physiological changes causing obstructed bowel movement. Moreover, the speed of the VCE advance is considered to be affected easily by hospitalization or previous surgery of the abdomen [32][33][34]. Therefore, the route selection for DBE should be estimated by both the location of the lesion, detected by computed tomography (CT) or ultrasound sonography, and the distance from the mouth or anus to the lesion, as determined by VCE [35] or enteroclysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that GTT affects CE completion 2,5,13,14. Moreover, other factors, such as aging,15,16 diabetes mellitus,14 hospitalization,16 and previous abdominal surgery17 were found to be associated with incomplete CE. We confirmed that mosapride citrate administration and GTT less than 45 minutes were independent predictors of the CE examination completion according to a logistic regression model.…”
Section: Discussionmentioning
confidence: 81%